Texture evolution during cold rolling of dilute Mg alloys. (November 2015) - Zeng, Z.R.; Bian, M.Z.; Xu, S.W.; Davies, C.H.J.; Birbilis, N.; Nie, J.F.
Graphical abstract: Abstract: Effects of alloying additions on deformation texture in Mg sheet alloys are still controversial. In this study, a quasi-in-situ electron backscatter diffraction method is used for the first time to monitor the texture evolution during the cold rolling process of Mg–Zn–Ca and Mg–Zn alloys. It is found that the Ca addition does not cause any texture weakening effect — it only delays the development of a strong basal texture by reducing the growth of deformation twins.